The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/02699050701822022
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric traumatic brain injury: A review of siblings’ outcome

Abstract: Theoretically driven, prospective, longitudinal research into sibling outcome following child TBI is a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Siblings may be affected emotionally and behaviorally when a brother or sister sustains a brain injury (Sambuco, Brookes, & Lah, 2008) and may experience nightmares and anxiety, which in turn may impact on behavior and sleep. This makes siblings an appropriate control group, which allows for some of the psychosocial impact of TBI within the family.…”
Section: Discussionmentioning
confidence: 99%
“…Siblings may be affected emotionally and behaviorally when a brother or sister sustains a brain injury (Sambuco, Brookes, & Lah, 2008) and may experience nightmares and anxiety, which in turn may impact on behavior and sleep. This makes siblings an appropriate control group, which allows for some of the psychosocial impact of TBI within the family.…”
Section: Discussionmentioning
confidence: 99%
“…Promising, but not yet validated [Conoley and Sheridan, 1996;Waaland, 1998;Ylvisaker and Feeney 1998;Laroi, 2003;Swift et al, 2003;Wade et al, 2003;Leith et al, 2004;Stancin et al, 2004;Wade et al, 2004Wade et al, , 2006aGan et al, 2006;Wade, 2006;Sambuco et al, 2008] Adjusting the child's environment…”
Section: Family Realignmentmentioning
confidence: 98%
“…When siblings of children with moderate and severe BI were compared to siblings of children with orthopedic injuries, researchers found that siblings of children with BI with subsequent behavioral difficulties were at risk for more negative sibling relationships and display of behavior problems [Swift et al, 2003]. Sambuco et al [2008] reviewed the literature on sibling outcomes following TBI sustained by a brother or sister. Their review extends the findings by Swift et al [2003], in that they concluded siblings of children with TBI were at risk for residual psychological distress, especially if the child with the injury displayed behavioral difficulties.…”
Section: Family Realignmentmentioning
confidence: 98%
“…Interactions among family members change rapidly and, often, for the worse; and new responsibilities are thrust upon the child or adolescent, who may be overwhelmed by feelings of guilt, anger or helplessness [2,6]. Our research project aims to develop and deliver educational material to youths faced with TBI of a family member.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%